2016
DOI: 10.1016/j.gaceta.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Opinions and practices regarding electronic cigarette use among Romanian high school students

Abstract: Health education programmes and regulatory interventions addressing e-cigarettes are needed in Romania. More research is necessary on how to develop effective public health messages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 14 publications
1
37
0
2
Order By: Relevance
“…In a recent study, 38.5% of Romanian 9th graders had ever tried e-cigarettes, 31.4% had tried cigars and 21.1% had tried a waterpipe [16]. Similar rates of e-cigarette use have been observed among adolescents in other Romanian and Eastern European locales [17,18]. Recently, Philip Morris announced that its plant in Otopeni (near Bucharest) will begin annual production of “heat-not-burn” tobacco products, serving a very large European and Asian market [19].…”
Section: Discussionmentioning
confidence: 73%
“…In a recent study, 38.5% of Romanian 9th graders had ever tried e-cigarettes, 31.4% had tried cigars and 21.1% had tried a waterpipe [16]. Similar rates of e-cigarette use have been observed among adolescents in other Romanian and Eastern European locales [17,18]. Recently, Philip Morris announced that its plant in Otopeni (near Bucharest) will begin annual production of “heat-not-burn” tobacco products, serving a very large European and Asian market [19].…”
Section: Discussionmentioning
confidence: 73%
“…With regard to smoking and alcohol use as well violence related behaviour, no significant differences were found between sport club participants and non-participants, while football players behaved differently than the other two groups with regard to several issues. Several studies underline that smoking among Romanian high school adolescents is an important public health problem while the use of electronic cigarettes is a new concerning issue [20,21]. In our study, football players had the tendency to declare less often smoking during lifetime (20% of the football players vs. half of the other two groups) and in the last month (20% of the football players vs. one third of the other two groups), as well as intention to smoke in the next year (7.5% of the football players vs. one out of three subjects from the other two groups).…”
Section: Discussionmentioning
confidence: 99%
“…None of the football players tried e-cigarettes, while half of the students from the other two groups did so, while around 13% of them used e-cigarettes in the last month. Another study performed among Romanian high school students (both girls and boys) in 2013 found a prevalence of e-cigarette use during lifetime and in the last month of 28.9% and 3%, but e-cigarette experimentation and use among adolescents is rising in several countries [21]. None of the football players declared consumption of alcohol drinks at least once a week, while the percentage of the other two groups who did so varied between 7% and 24%, depending on the type of alcohol drink.…”
Section: Discussionmentioning
confidence: 99%
“…Estelle Dauchy 1 , Olga Knorre 2 1 Campaign for Tobacco Free Kids, United States, 2 Campaign for Tobacco Free Kids, Portugal Objective To present and assess regulations related to NGP (E-Cigs and HTP) in Eastern Europe; To question and discuss what model / position we think is best (at least in the short term). Panelists will present and share perspectives on the feasibility of tax policy and on the material needed to support policy (data / research).…”
Section: Taxation and Price Regulations Of New Generations Productsmentioning
confidence: 99%